Estudio de prefactibilidad para la creación de un hotel turístico ecológico en el cantón Santa Cruz de la provincia de Galápagos - Caicedo Medina, Betsabel Roxana (2019)
Tourism is the highest point to generate income in the country, in recent periods has had a favorable growth even more in the province of Galapagos, because the demand for hotel services has been growing it is necessary to offer a different place with a new style that fits the needs of tourists. Referring to this idea it was necessary to carry out the present research project that is aimed at a pre-feasibility study for the creation of an ecological hotel located in the upper part of the Santa Cruz Canton in the Galapagos Islands, the hotel service on the Island currently only offers lodging which allows us to innovate with different services with sustainable and sustainable resources that help to take care of the environment, for this a pre-feasibility study will be carried out that demonstrates the viability of the project through economic and financial studies…..